Helicobacter pylori eradication may influence timing of endoscopic surveillance for gastric cancer in patients with gastric precancerous lesions: A retrospective study. Issue 4 (January 2018) - Dore, Maria Pina; Cipolli, Alice; Ruggiu, Matteo Walter; Manca, Alessandra; Bassotti, Gabrio; Pes, Giovanni Mario
Abstract : Abstract: Chronic atrophic gastritis and intestinal metaplasia related to Helicobacter pylori infection, are major risk factors for gastric adenocarcinoma. Eradication of H pylori and endoscopy surveillance of precancerous lesions may reduce the risk and/or lead to early detection of gastric cancer improving survival. In this study, the progression of precancerous lesions after H pylori treatment was evaluated. Patients with incomplete or complete intestinal metaplasia and/or gastric atrophy at the index endoscopy, were examined for the extension/histological worsening of precancerous lesions at the endoscopy surveillance for gastric cancer. Progression of lesions was evaluated according to H pylori status, age, and sex. Cox proportional hazard regression model and Kaplan–Meier curves were used to evaluate the strength of predictors for lesions progression. Among 105 patients (61 women) H pylori negative patients showed a milder worsening of gastric lesions between index and surveillance endoscopy compared with patients positive for the infection (log-rank test: P  < .0001, P  = .012, and P  = .032 for antrum, angulus, and corpus, respectively). The Cox regression model showed persistence of H pylori infection (hazard ratio = 4.436; P  < .0001) as the only relevant factor for lesion progression, whereas age >65 years and sex were not significant predictors. According to literature our results demonstrate that H pylori eradication is the major factor able to delay gastric precancerous lesions progression. Time interval for endoscopic surveillance in patients negative for H pylori infection and with gastric precancerous lesions may be extended.